Transforming higher education with robotic process automation: enhancing efficiency, innovation, and student-centered learning - Vivek Bhardwaj; Mukesh Kumar (Discover Sustainability)
Abstract Robotic Process Automation (RPA) is transforming the education sector by automating repetitive, rule-based tasks previously carried out by humans. This paper investigates the applications, benefits, challenges, and implications of RPA in education, focusing on its impact on administrative processes, student support services, and teaching methodologies. By analyzing 54 studies conducted between 2020 and 2024, this research explores how educational institutions have adopted RPA to enhance operational efficiency. Case studies reveal common success factors, including significant time savings, error reduction, and improved satisfaction for both students and staff. RPA has enabled institutions to streamline administrative workflows, optimize resource management, and offer personalized learning experiences. However, challenges such as implementation costs, data security, and the need for effective change management are also addressed. Additionally, this paper examines ethical concerns, particularly those surrounding job displacement and privacy. The findings underscore the transformative potential of RPA while highlighting the complexities of its integration into educational settings. The methodology followed PRISMA guidelines, with a systematic search of academic databases including IEEE Xplore, Scopus, Web of Science, and Google Scholar. Inclusion criteria focused on studies published between 2020 and 2024 that addressed RPA applications in education. Data analysis was conducted using thematic synthesis to identify key trends across the selected studies.